Engineered cord blood megakaryocytes evade killing by allogeneic T-cells for refractory thrombocytopenia - Kumar, Bijender; Afshar-Kharghan, Vahid; Mendt, Mayela; Sackstein, Robert; Tanner, Mark R.; Popat, Uday; Ramdial, Jeremy; Daher, May; Jimenez, Juan; Basar, Rafet; Melo Garcia, Luciana; Shanley, Mayra; et al. (Frontiers in Immunology, 2022)
The current global platelet supply is often insufficient to meet all the transfusion needs of patients, in particular for those with alloimmune thrombocytopenia. To address this issue, we have developed a strategy employing a combination of approaches to achieve more efficient production of functional megakaryocytes (MKs) and platelets collected from cord blood (CB)-derived CD34+ hematopoietic cells. This strategy is based on ex-vivo expansion and differentiation of MKs in the presence of bone marrow niche-mimicking mesenchymal stem cells (MSCs), together with two other key components: (1) To enhance MK polyploidization, we used the potent pharmacological Rho-associated coiled-coil kinase (ROCK) inhibitor, KD045, resulting in liberation of increased numbers of functional platelets both in-vitro and in-vivo; (2) To evade HLA class I T-cell-driven killing of these expanded MKs, we employed CRISPR-Cas9-mediated β-2 microglobulin (β2M) gene knockout (KO). We found that coculturing with MSCs and MK-lineage-specific cytokines significantly increased MK expansion. This was further increased by ROCK inhibition, which induced MK polyploidization and platelet production. Additionally, ex-vivo treatment of MKs with KD045 resulted in significantly higher levels of engraftment and donor chimerism in a mouse model of thrombocytopenia. Finally, β2M KO allowed MKs to evade killing by allogeneic T-cells. Overall, our approaches offer a novel, readily translatable roadmap for producing adult donor-independent platelet products for a variety of clinical indications.